1997
DOI: 10.1038/sj.bmt.1701024
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis in marrow transplant patients: prevalence at autopsy and risk factor analysis

Abstract: Summary:recognize the symptoms of pancreatitis in this population. However, marrow transplant patients may be predisposed to developing pancreatitis due to the high prevalence of Pancreatitis has been described as an infrequent complication of marrow transplantation. This study investibiliary sludge and sonographic biliary tract abnormalities, 2,3use of irradiation and cytotoxic drugs in the conditioning gated the prevalence of pancreatitis at autopsy in marrow transplant patients and determined risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 1 publication
2
33
1
1
Order By: Relevance
“…1,19 Earlier studies in children measured the incidence for pancreatitis and found it to be 2.1-3.5%. 19,36 The results obtained here are similar with 4.9% developing acute pancreatitis and was not a major contributor to morbidity or mortality in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,19 Earlier studies in children measured the incidence for pancreatitis and found it to be 2.1-3.5%. 19,36 The results obtained here are similar with 4.9% developing acute pancreatitis and was not a major contributor to morbidity or mortality in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the published data regarding these complications comes from adult studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] A paucity of information exists in the published literature regarding the incidence, range and severity of gastrointestinal (GI) complications in pediatric patients in the immediate post-BMT period. 19,20 The majority of the pediatric studies examined specific complications such as veno-occlusive disease (VOD), acute pancreatitis or typhilitis in fairly homogeneous patient populations.…”
mentioning
confidence: 99%
“…The association of acute pancreatitis with severe gastrointestinal or liver aGVHD has been reported. 37,38 Marrow transplant recipients may be predisposed to developing pancreatitis because of biliary sludge, use of irradiation or cytotoxic drugs in the conditioning regimen, prolonged medication with corticosteroids and CSA, and viral infections. 39,40 Our data do not show a relation of pancreatitis to these factors, although in three patients adenovirus was detected in stool and/or gastric secretion only during the course of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…5 In an autopsy series of allo-SCT patients from Seattle, signs of pancreatitis were found in 28% of allo-SCT recipients, although a premortem clinical diagnosis was made in only 10% of those patients. 6 Two cases of pancreatitis apparently related to tacrolimus have been reported after liver transplantation. 7,8 However, to the authors' knowledge, tacrolimus-associated pancreatitis has not been reported yet in allo-SCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although pancreatitis seems much more common after intravenous pentamidine, a few cases of aerosolized pentamidine-related pancreatitis have been reported. 9,10 Intravenous pentamidine-associated pancreatitis appears to develop after an accumulated dose of more than 1 g, whereas this patient had received a cumulative dose of 300 mg of inhaled drug at the time of symptom onset.…”
Section: Discussionmentioning
confidence: 99%